Divergent trends in functional and phylogenetic structure in reptile communities across Africa. Issue 1 (December 2018) - Ramm, Till; Cantalapiedra, Juan; Wagner, Philipp; Penner, Johannes; Rödel, Mark-Oliver; Müller, Johannes
Abstract Despite extensive research on ecological community compositions, general patterns across large-scale environmental gradients have remained unclear. A widely used explanatory model is the stress dominance hypothesis (SDH), predicting that the relative influence of environmental filtering is greater in stressful habitats while competition is more important in benign environments. Here, we test the SDH using African squamates as a model system to facilitate general predictions on community structures amidst changing global environments. For the first time we investigate changes in functional, phylogenetic and species diversity across continental, environmental gradients within a multidimensional, phylogenetically informed approach. Results suggest that phylogenetic patterns of African squamates were likely shaped by clade-specific biogeographic histories, whereas functional structure reflects SDH predictions. We further detected significant structuring at both local and regional spatial scales, emphasizing the impact of regional-historical processes on local assemblages, and the need for broad conceptual frameworks to detect general patterns of community composition. The biogeographic drivers of reptile diversity are poorly understood relative to other animal groups. Here, using a dataset of distributions of African squamates, the authors show that environmental filtering explains diversity in stressful habitats while competition explains diversity in benign habitats.